Changes in Anterior Chamber Parameters Measured by Pentacam in Coronavirus Disease 2019 Infection: A Longitudinal Study - Saeed Shokoohi-Rad; Mojtaba Abrishami; Elham Bakhtiari; Asma Payandeh; Hamid-Reza Heidarzadeh (Journal of Ophthalmology)
Purpose. To evaluate changes in anterior segment parameters measured by imaging in coronavirus disease 2019 (COVID-19) infection. Methods. This longitudinal observational study included patients who recovered from COVID-19. All subjects exhibited a confirmed diagnosis of COVID-19 with a positive result of nasopharyngeal reverse transcription-polymerase chain reaction evaluation. Corneal Pentacam (Oculus, Dutenhofen, Germany) imaging was performed at least two weeks after recovery from systemic COVID-19. Measurements were repeated one and three months later. Results. A total of 20 patients, 11 (55%) of whom were females, with a mean age of 35.5 ± 7.1 years (age range: 25–51 years) recovered from nonhospitalized COVID-19 infection, were enrolled in this study. An increase in the keratometry mean front, keratometry mean back, cornea volume, and anterior chamber depth was observed in the longitudinal evaluation; however, they showed no statistical significance. The anterior chamber volume was statistically increased at three-month follow-up, compared to baseline (baseline: 177.8 ± 36.68 mm3; three months: 182.25 ± 39.58 mm3, P=0.048). Conclusion. COVID-19 infection may affect the cornea and anterior segment.